Estimating Labor Market Slack, U.S. 1994-2019 - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2019)
U3, the official unemployment rate, is an inadequate gauge of labor-market slack and the extent to which it misinforms varies substantially over the business cycle. The U6 unemployment rate is usually about 4 percentage points above U3. However, during the Great Recession it exceeded U3 by 7 percentage points for three years. Moreover, the U6-U3 gap is magnified among disadvantaged groups such as minorities, youth, and for the less educated. For instance, in January 2011 the U6-U3 gap among African American youth was 17.9 pps as U6 climbed to 47.5% and was similarly large among African Americans without a high-school diploma.
Keywords: J40; J49; J69; 330; unemployment; U6; unemployment by ethnicity; discouraged workers; labor market slack